Spatial Analysis To Predict Conservation Heritageâ€™s Damage Of â€œImogiri Gravesâ€ By Using Microtremor Measurements - Gunawan, Arif; Wibowo, Nugroho Budi (Jurnal Tata Kota dan Daerah, 2013)
The paper gives you a description more comprehensive views to learn spatial aspect in relating to the effects of earthquake damage in human civilization which is one of them is for Imogiri Graves Area. These ones are important place for Mataram Kingdom funerals. Based on last observation, this location was partially destroyed by earthquake disaster like other places in Bantul Regency. The theories could be embedded in this cases which consists of Kanai methods for Ground Acceleration and Ground Shear Stress (GSS). Then, deriving from those we can analyze the spatial aspect of disaster prone area which emphasizing into figure out Peak Ground Acceleration (PGA) and Seismic Susceptible Index (Kg)-Ground Shear Stress (GSS) as well. The results are: (1) PGAâ€™s area are showed 129-174 gal and directly connected to damage ratio for buildings; (2) Seismic Susceptible Indexes (Kg) are below 20 which means Imogiri area was a safe zone (with low-risk susceptible).Keywords: Spatial, Microtremor, PGA, Kg, Imogiri